Impact of gadolinium‐based contrast agent in the assessment of Crohn's disease activity: Is contrast agent injection necessary?. Issue 3 (6th August 2015) - Quaia, Emilio; Sozzi, Michele; Gennari, Antonio Giulio; Pontello, Michele; Angileri, Roberta; Cova, Maria Assunta
Abstract : Purpose: To determine whether magnetic resonance enterography (MRE) performed without intravenous contrast injection is diagnostically noninferior to conventional contrast‐enhanced MRE (CE‐MRE) in patients with Crohn's disease (CD). Materials and Methods: This was an Institutional Review Board (IRB)‐approved retrospective study. Ninety‐six patients (52 male and 44 female; 47.18 years ± 13.6) with a diagnosis of CD underwent MRE at 1.5T including T 2 ‐weighted single‐shot turbo‐spin‐echo, T 2 ‐weighted spectral fat presaturation with inversion recovery (SPAIR), T 1 ‐weighted balanced fast‐field‐echo MR sequences, and CE‐MRE consisting in T 1 ‐weighted breath‐hold THRIVE 3D MRI sequences after administration of gadobenate dimeglumine (0.2 mL/kg of body weight). Unenhanced MRE, CE‐MRE, and unenhanced MRE plus CE‐MRE were reviewed in separate sessions with blinding by two readers in consensus, and subsequently by two other readers independently considering a subgroup of 20 patients. Crohn's Disease Endoscopic Index of Severity (CDEIS) and/or histologic analysis of the surgical specimen were considered as reference standards for the assessment of inflammatory activity. Results: Patients revealed prevalently active ( n = 55 patients) or quiescent CD ( n = 41 patients). The agreement between unenhanced MRE vs. CE‐MRE in interpreting active bowel inflammation was 96% (123/128 bowel segments; one‐sided 95% confidence interval [CI], >94.4%). Unenhanced MRE vs. CE‐MRE vs. unenhanced MRE plus CE‐MRE revealed a diagnostic accuracy of 93% [90/96] vs. 92% [88/96] vs. 97% [93/96] ( P > 0.05) in the diagnosis of active CD. Interreader agreement was very good for all variables (κ value = 0.8–0.9) except for the measurement of the length of disease (κ value = 0.45). Conclusion: Unenhanced MRE was noninferior to CE‐MRE in diagnosing active inflammation in patients with CD. J. MAGN. RESON. IMAGING 2016;43:688–697.